FUNGSI MANAJERIAL KEPALA MADRASAH DALAM MENCIPTAKAN MADRASAH EFEKTIF MADRASAH TSANAWIYAH NEGERI 2 KOTAWARINGIN TIMUR - Errita Malati (UNISAN JURNAL, 2024)
This research aims to investigate the extent of the role of the Madrasah Head in creating an effective learning environment at Madrasah Tsanawiyah Negeri 2 East Kotawaringin. This research uses a qualitative approach with a case study approach to gain an in-depth understanding of how Madrasah Principals utilize their managerial functions in creating an effective learning environment for students. Data was collected through observation, interviews and document analysis, and analyzed using qualitative data analysis techniques. The research results show that the Head of Madrasah Tsanawiyah Negeri 2 East Kotawaringin is able to utilize his managerial functions effectively to create an effective learning environment for students. Careful planning, efficient organization, clear direction, quality supervision, continuous evaluation, and human resource development are some of the strategies used by Madrasah Heads in creating an effective learning environment. The role of the Madrasah Head in planning, organizing, directing and supervising activities at Madrasah Tsanawiyah Negeri 2 East Kotawaringin can also be said to be effective. Through the ability to carry out their functions well, the Madrasah Principal is able to create an effective and quality learning environment for students. With an effective learning environment, it is hoped that students can develop their potential to the maximum and be able to compete in an increasingly competitive era of globalization. Human resource development carried out by Madrasah Heads has also been proven to be able to improve the quality of educational services for students. Through various HR development programs, the Madrasah Head succeeded in increasing the competency, motivation and performance of all madrasah staff. This creates a conducive learning environment for students to develop their potential optimally. In this way, the Head of Madrasah Tsanawiyah Negeri 2 East Kotawaringin can be used as an example for other madrasah heads in utilizing their managerial functions and human resource development to create an effective and quality learning environment for students.